Fabrication of devices featuring covalently linked MoS2-graphene heterostructures - Vázquez Sulleiro, Manuel; Develioglu, Aysegul; Quirós-Ovies, Ramiro; Martín-Pérez, Lucía; Martín Sabanés, Natalia; Gonzalez-Juarez, Maria Lourdes; Gómez, I Jénnifer; Vera-Hidalgo, Mariano; Sebastián, Víctor; Santamaría, Jesús; Burzurí, Enrique; Pérez, Emilio M (Nature chemistry, 2022)
The most widespread method for the synthesis of 2D-2D heterostructures is the direct growth of one material on top of the other. Alternatively, flakes of different materials can be manually stacked on top of each other. Both methods typically involve stacking 2D layers through van der Waals forces-such that these materials are often referred to as van der Waals heterostructures-and are stacked one crystal or one device at a time. Here we describe the covalent grafting of 2H-MoS2 flakes onto graphene monolayers embedded in field-effect transistors. A bifunctional molecule featuring a maleimide and a diazonium functional group was used, known to connect to sulfide- and carbon-based materials, respectively. MoS2 flakes were exfoliated, functionalized by reaction with the maleimide moieties and then anchored to graphene by the diazonium groups. This approach enabled the simultaneous functionalization of several devices. The electronic properties of the resulting heterostructure are shown to be dominated by the MoS2-graphene interface.